Cooperation among Local Governments in Realizing the National Strategis Area Development in Bangkalan Regency - Djaja, Tamar (FIA UB, 2018)
The existence of National Strategis Area (NSA) in Bangkalan should not be ignored, but should be considered as a potential material that must be managed to create a progressive development for the people of Bangkalan Regency. Basically, the Bangkalan regency government can not carry out its own development, there must be a cooperation with the other that able to support the development optimization. Inter-regional cooperation for Bangkalan Regency has a very potential role, especially in the process of NSA development so that NSA will be able to become a trigger point in the development process. General question that should find the answer by researchers is